La semántica - Baena, Luis Ángel; Rangel, Daniel (Lenguaje, 1972)
El artículo titulado "La semántica" (https://doi.org/10.25100/lenguaje.v1i4.13811) publicado en el Vol. 1 Núm. 4 (1972) No cuenta con resumen